N,N′-Bis[(2-methylphenyl)sulfonyl]adipamide - Rodrigues, Vinola Z. (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, C20H24N2O6S2, comprises one half-molecule, the remaining portion being generated via an inversion centre. The dihedral angle between the plane of the benzene ring and the SO2—NH—C(O)—C—C segment is 89.9 (1)°. In the crystal, intermolecular N—H⋯O(S) hydrogen bonds link the molecules into infinite chains in [101].